Innovative Surgical Approaches for Locally Advanced Hepatic Malignancy - Yu, Young-Dong; Kim, Dong-Sik (Digestive Disease Interventions, 2020)
Primary and secondary liver tumors are among the most common tumors in humans. Liver resection and liver transplantation are used to treat these malignancies. However, in many patients with locally advanced malignancy, it is not possible to resect these tumors using conventional techniques due to their enormous size or complex location. Refinements of surgical techniques have led to great improvements in terms of postoperative outcome and long-term survival in the past decades. This review explores innovative technologies in liver surgery, including both resection and transplantation, and their potential role in treating locally advanced hepatic malignancy. A number of innovative surgical techniques such as associating liver partition and portal vein ligation for liver surgery (ALPPS), ex vivo resection, ante situm liver resection, liver resection using extracorporeal hepatic venous bypass, and resection and partial liver segment 2/3 transplantation with delayed total hepatectomy (RAPID) have been developed to overcome the barriers of conventional liver resection and may offer acceptable outcomes for well-selected patients with locally invasive tumors that are otherwise inoperable by conventional techniques.
Keywords: liver; surgical; techniques; innovative